2015
DOI: 10.3168/jds.2015-9353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a second treatment with prostaglandin F2α during the Ovsynch protocol on luteolysis and pregnancy in dairy cows

Abstract: The main objective of this study was to evaluate the effect of a second treatment with prostaglandin F2α (PGF) during Ovsynch on regression of the corpus luteum (CL) and on fertility to the timed artificial insemination. Two experiments were performed. In both experiments, cows were randomized to receive (1) no additional treatments with PGF=1 PGF, or (2) a second PGF treatment at 24h after the first PGF treatment=2 PGF. The first experiment (n=344 synchronized lactating dairy cows that received artificial ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 51 publications
8
86
1
3
Order By: Relevance
“…luteolysis, thereby increasing P/AI after first TAI using a Double-Ovsynch protocol (Wiltbank et al, 2015) and increasing P/AI to Resynch TAI (Carvalho et al, 2015a;Santos et al, 2016). Thus, the association of low P4 at the onset of or during the Ovsynch protocol with poor fertility to TAI may be a result of incomplete luteal regression rather than an effect on the preovulatory follicle, and our results would support this idea.…”
Section: Pregnancy Outcomessupporting
confidence: 78%
See 2 more Smart Citations
“…luteolysis, thereby increasing P/AI after first TAI using a Double-Ovsynch protocol (Wiltbank et al, 2015) and increasing P/AI to Resynch TAI (Carvalho et al, 2015a;Santos et al, 2016). Thus, the association of low P4 at the onset of or during the Ovsynch protocol with poor fertility to TAI may be a result of incomplete luteal regression rather than an effect on the preovulatory follicle, and our results would support this idea.…”
Section: Pregnancy Outcomessupporting
confidence: 78%
“…Second, we included an additional PGF 2α treatment 24 h after the first during the Breeding-Ovsynch portion of the Double-Ovsynch protocol, as first described by Brusveen et al, (2009) to induce complete luteal regression by G2. Incomplete luteal regression, measured as P4 ≥ 0.4 ng/mL at G2, is associated with decreased fertility at first and second and greater TAI, and cows that received a second PGF 2α treatment 24 h after the first during an Ovsynch protocol for first or second and greater TAI had decreased incomplete luteal regression and increased fertility to TAI (Carvalho et al, 2015a;Wiltbank et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, in lactating Holstein cows, a second treatment of dinoprost tromethamine (+PGF2α; 24 h apart) increased the percentage of cows that had complete luteal regression (95.6%) compared with control cows (84.6%). Although one study found no detectable effect of the additional PGF2α on P/AI (control = 41.5% vs. +PGF2α = 44.7%; P = 0.34; Brusveen et al, 2009), recent studies have found significant improvements in P/AI when a second PGF2α treatment is given, particularly in multiparous cows (Carvalho et al, 2015;Wiltbank et al, 2015). Therefore, complete luteolysis is essential to optimize ovulation and fertility to a FTAI protocol.…”
Section: Corpus Luteum Function Luteolysis and Growth And Ovulationmentioning
confidence: 99%
“…Fixed‐time artificial insemination (FTAI) programs have been developed to synchronise ovulation, allowing cows to be inseminated on a given day, increasing the probability of submission for service once a decision has been made that they are eligible to be bred . The use of hormonal manipulation of the reproductive cycle can improve reproductive performance by decreasing the interval from calving to first service .…”
mentioning
confidence: 99%